Clouds over the Mediterranean: Israeli Women’s Writing in the Shadow of the Female Gothic - Keren, Nitza (MiKAN, 2010)
This essay follows the routes of the Female Gothic in Hebrew Literature, exploring its marks on contemporary Israeli women writers: Amalia Kahana-Carmon, Hanna Bat Shahar and Savyon Liebrecht, thus raising an issue overlooked by local literary criticism. Hanna Bat Shahar’s haunted world, as expressed in the collection of stories To Call the Bats, is presented in the context of Amalia Kahana-Carmon’s unique description of feminine poetics which compares women’s writing to the bat’s song – indiscernible to the hegemonic ears. Kahana-Carmon’s story “Scenes from the House of the Blue-Painted Stairs”, with its enchanted attic, serves as another example of feminine poetics, manifesting Elaine Showalter’s description of the underground female plots, and so does the story of the girl who is imprisoned in the remote castle Up in Montifer. The testimony of the outcast woman who lives in the wilderness, presented in Savyon Liebrecht’s story “Festival of the Two Worlds” concludes the essay. Representing the eccentric woman who is excluded from hegemonic society, Liebrecht enables her, along with other female characters occupying her stories, to present their alibi.